2016
DOI: 10.15570/actaapa.2016.21
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological characteristics of perianal streptococcal dermatitis: a retrospective study of 105 patients in a 10-year period

Abstract: Beta-hemolytic streptococci (BHS) are the most common causative agents of perianal streptococcal dermatitis (PSD). This study evaluates the distribution of BHS isolates in perianal bacterial cultures. We retrospectively reviewed microbiological results for perianal BHS that were isolated in our laboratory between 2006 and 2015. We identified a total of 105 BHS isolates from rectal swabs and swabs of clinically intact perianal skin. The majority of BHS were of group A (GABHS) (73/105; 69.5%), followed by group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 20 publications
(67 reference statements)
2
13
0
Order By: Relevance
“…This is in contrast to PSD in children, in which group A β-haemolysing Streptococci (GABHS) are predominant. This difference in groups of BHS in association with age also was observed by Sterbenc et al [3]. While children with PSD can be cured in almost all cases by eradication of Streptococci with systemic antibiotic treatment, we demonstrated that in adults, a substantial percentage of patients require continuing or further treatment of their concomitant anorectal disease in addition to treatment of PSD to achieve freedom from symptoms.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…This is in contrast to PSD in children, in which group A β-haemolysing Streptococci (GABHS) are predominant. This difference in groups of BHS in association with age also was observed by Sterbenc et al [3]. While children with PSD can be cured in almost all cases by eradication of Streptococci with systemic antibiotic treatment, we demonstrated that in adults, a substantial percentage of patients require continuing or further treatment of their concomitant anorectal disease in addition to treatment of PSD to achieve freedom from symptoms.…”
supporting
confidence: 88%
“…In contrast to children, in whom PSD was mostly caused by GABHS, adult PSD was associated with GBBHS. This finding was confirmed by Sterbenc et al [3]. In paediatric PSD patients, eradication by systemic antibiotics lead to an almost 100% cure rate.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations